Characterization and optimization of the LAC4 upstream region for low‐leakage expression in Kluyveromyces marxianus. Issue 4 (2nd December 2021) - Liu, Benxin; Wu, Pingping; Zhou, Jungang; Yin, Anqi; Yu, Yao; Lu, Hong
Abstract: Kluyveromyces marxianus is a promising host for the production of heterologous proteins, chemicals, and bioethanol. One superior feature of this species is its capacity to assimilate lactose, which is rendered by the LAC12–LAC4 gene pair encoding a lactose permease and a β‐galactosidase enzyme. Little is known about the regulation of LAC4 in K. marxianus . In this study, we showed the presence of weak glucose repression in the regulation of LAC4 and that might contribute to the leaky expression of LAC4 in the glucose medium. In a mutagenesis screen of 1000‐bp LAC4 upstream region, one mutant region, named H1, drove low‐leakage expression of a URA3 reporter gene in glucose medium. Two mutations inside a polyadenosine stretch (poly(A)) of 5′ UTR were major contributors to the low‐leakage phenotype of H1. H1 directed low‐leakage expression of GFP on a plasmid and that of LAC4 in situ in the glucose medium, which was not due to the reduction of mRNA levels. Meanwhile, H1 did not affect the induction of GFP or LAC4 by lactose. Cre recombinase expressed by H1 caused lower toxicity in the repressive condition and achieved higher yield after induction, compared with that expressed by a wild‐type LAC4 upstream region or a strong INU1 promoter. Our study suggested that poly(A) inside 5′ UTR played a role in regulating the expression of LAC4 in the repressive condition. Meanwhile, H1 provided a base for the development of a strict inducible system for expressing industrial proteins, especially toxic proteins. Take Away: Presence of weak glucose repression of LAC4 in Kluyveromyces marxianus . Mutations inside 5′ UTR of LAC4 reduced leaky expression in repressive conditions. Poly(A) inside 5′ UTR played roles in regulating the expression of LAC4 . Low‐leakage LAC4 upstream region could be applied in expressing toxic proteins. Abstract : In K. marxianus, mutations interrupting a poly(A) stretch inside the 5'UTR of LAC4 lead to the low leakage expression in the glucose medium. The findings will benefit the development of a strict inducible system for expressing industrial proteins, especially toxic proteins.